The Ever-Changing Rules of Hajj in South Sulawaesi 1947-1950 - Faturrahman, Ahmad; Riswandi, Riswandi; Manalu, Sri Rahmayani (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article aims to explain the administrative rules for the implementation of the pilgrimage in 1947-1950, the period of the State of East Indonesia, which was always changing. This study uses historical methods consisting of heuristics, source criticism, interpretation and historiography. The data used is in the form of archives and books. The results of the study found that the factors that resulted in the regulations issued by the State of East Indonesia government were always different every year due to the social aspect which was marked by the number of registrants who exceeded the quota given so that the State of East Indonesia government had to pay attention to applicants who were on the waiting list, in contrast to political aspects in the form of the entry of new areas controlled by the Dutch so that quotas must also be given to these regions.Keywords: Hajj Administration, State of East Indonesia, South Sulawesi.